WAYS OF STRATEGIC DEVELOPMENT AND INCREASE OF COMPETITIVENESS OF AGRICULTURAL ENTERPRISES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article describes the effectiveness of strategic management of agricultural enterprises, the factors influencing it, improving the efficiency and competitiveness of agricultural enterprises and improving the organizational and economic mechanisms to increase competitiveness.